National interests and human needs of civil society as the fundamental principles of national sovereignty - Волошина, Юлія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with an understanding of modern jurisprudence categories of «national interest», «human needs and civil society» as the fundamental principles of national sovereignty and important determinant of national revival state. The analiz we did in our article gave us an opportunity to see the sense of national interest through the different permanent factors, such as economical, social, ethnic and political precondition. The main attention we concentrate on cultural and psychological development of nation interest, as a part of national spiritual values. In the final analysis we can propose the definition for the term “national interest”. In our opinion its proceed from the assumption that the main part of interest is material and cultural needs of the people, which manifest itself through spiritual value and direct attention at conservation and creation the favourable, necessary conditions for stable existence and development.